Agricultural technology: Why does the level of agricultural production remain low despite increased investments in research and extension? - Rowena T. Baconguis (Philippine Institute for Development Studies (PIDS), 2022)
Adoption of new practices and technologies influences farm productivity and agricultural growth. Countries invest in research and extension to ensure continuous growth both at the farm and industry level. This chapter investigates agricultural technology production, its knowledge transfer, and farm and industry level performance. It is divided into three sections: (1) the structure and the financing of agricultural technology production and transfer, (2) technology promotion and adoption (3) conclusions and recommendations for the Philippine agricultural technology innovation systems. The study used the agricultural innovation systems (AIS) as lens in investigating the agricultural performance of the country, focusing on rice and swine industry. AIS examines the institutions and policies that create and put innovations to economic use. In AIS, adoption studies cannot be separated from the research and extension functions of the government as they are presumed to directly affect the uptake of these innovations. The study used descriptive - explanatory research design to explain the agricultural performance by gathering official statistics from various government agencies and data repositories, reviewing published studies, and conducting key informant interviews. Secondary data review and key informant interviews were conducted to gather institutional and farm level data on rice farmers and swine raisers, two industries which contribute significantly to the gross value added. [...]
Keywords: 330; technological promotion; adoption; agricultural growth; agricultural innovationsystems; agricultural performance